If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -5x + -1(8x + 6) = 0 Reorder the terms: 7x + -5x + -1(6 + 8x) = 0 7x + -5x + (6 * -1 + 8x * -1) = 0 7x + -5x + (-6 + -8x) = 0 Reorder the terms: -6 + 7x + -5x + -8x = 0 Combine like terms: 7x + -5x = 2x -6 + 2x + -8x = 0 Combine like terms: 2x + -8x = -6x -6 + -6x = 0 Solving -6 + -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -6x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -6x = 0 + 6 -6x = 0 + 6 Combine like terms: 0 + 6 = 6 -6x = 6 Divide each side by '-6'. x = -1 Simplifying x = -1
| 8+2y+2x=0 | | 14+m=n | | 6x-(5x+1)= | | 59x-(39x-78)= | | 15x+20y=360 | | 25(2x-3)=125 | | 13x+7=6x+7 | | 2*x-2=22 | | t+.08t=37 | | 6(13+4)= | | 3x+7=-3x+2+2+6x | | 5x^2+4x+1=225 | | 73=2x+7(x-5) | | 6(3.2m-1)=3.6 | | y=-3*1-4 | | (-4x-2)+(13x+1)= | | .111y-4=-9 | | y+8=12(x-6) | | 4*6+x=24 | | 50+75=359 | | 80x+2x=1000 | | (6x-7)(6x-7)=0 | | -2x+15=18 | | -28+s=15 | | 5*2x-1=45 | | -(5x-2y+7z)= | | 3*5+2=4*5-3 | | 4=ts+3.75 | | X+3*9=63 | | 4=t+3.75s | | X=10(140-70)+40 | | 3*-5+2=4*-5-3 |